2011
DOI: 10.1017/s0033291711002844
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of post-traumatic stress disorder among adolescents after the Wenchuan earthquake in China

Abstract: PTSD symptoms changed gradually at various stages after the earthquake. Depression symptoms were predictive of PTSD symptoms in the 18-month follow-up study. Other predictors of PTSD symptoms included female gender and being a child with siblings. The results of this study may be helpful for further mental health interventions for adolescents after earthquakes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
117
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 29 publications
5
117
1
4
Order By: Relevance
“…Among these risk factors, pre-existing child characteristics (e.g., gender, age, and prior exposure to traumatic events) have been well studied. Many studies found that girl survivors of disasters had a greater risk than boy survivors to develop PTSD and depressive symptoms [8,[17][18][19], although some studies did not find significant gender differences [18,20]. With regard to the association between age and PTSD symptoms, the results have been inconsistent across studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these risk factors, pre-existing child characteristics (e.g., gender, age, and prior exposure to traumatic events) have been well studied. Many studies found that girl survivors of disasters had a greater risk than boy survivors to develop PTSD and depressive symptoms [8,[17][18][19], although some studies did not find significant gender differences [18,20]. With regard to the association between age and PTSD symptoms, the results have been inconsistent across studies.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the association between age and PTSD symptoms, the results have been inconsistent across studies. Some studies indicated that age was not significantly related with PTSD after traumatic events [19,21], whereas other studies showed that older children had more severe symptoms than did younger children [4,22,23]. In a recent meta-analysis, Trickey et al [16] concluded that age's main effect was close to zero, but it may play a moderating role in the relationship between gender and PTSD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported before (25), the population was from a boarding high school after the 2008 Wenchuan earthquake. The devastating earthquake occurred in the afternoon of 12 May 2008, measuring 8.0 on the Richter scale and led to 69,227 deaths, 17,923 missing and 374,643 injured.…”
Section: Study Populationmentioning
confidence: 68%
“…The present study was to test the hypothesis. In fact, we had a population of high school students experiencing the 2008 Wenchuan earthquake, which we had explored the PTSD characteristics in 2008 and 2009, and reported them (25). We also had measured the plasma lipids profiles after sampling in 2008 (26).…”
Section: Introductionmentioning
confidence: 99%